Exploring English Teachers’ Perceptions and Experiences With AI-Assisted Module Creation (A Case Study of Perplexity AI in The Merdeka Curriculum Framework) - Zeni Fibriani (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2025)
This qualitative case study examines English teachers’ perceptions and experiences with AI-assisted module creation using Perplexity AI within the Merdeka Curriculum framework at MTsN 2 Blitar, Indonesia. The increasing demand for innovative, curriculum-aligned teaching materials and the growing integration of artificial intelligence in education have elevated the importance of incorporating digital tools into teachers’ professional practices. The research aimed to explore how Perplexity AI supports and transforms the module creation process, how teachers perceive the impact and challenges of using AI, and to what extent the resulting modules align with the Merdeka Curriculum objectives. Data were collected through semi-structured interviews with three English teachers, classroom observations of the module development workflow, and a detailed analysis of AI-generated and teacher-adapted modules. Thematic analysis revealed that teachers perceive Perplexity AI as highly empowering, reporting substantial time savings, enhanced confidence, and increased motivation to innovate instructional practices. Notably, module preparation time was reduced from several days or weeks to just 1–2 hours. Teachers valued the intuitive design, rapid content generation, and support for diverse assessment types, while emphasizing the ongoing need for critical review and contextual adaptation. Challenges included the need for precise prompts, the requirement for manual integration with local content, and managing the risk of over-reliance on technology. The study highlights the pivotal role of teacher agency and adaptation in ensuring that AI-generated modules are relevant, comprehensive, and contextually appropriate. The findings provide practical insights for educators and policymakers supporting technology integration in English curriculum development and underscore the critical balance between technological affordance and pedagogical expertise.